Hypoxia-regulated human periodontal ligament cells via Wnt/β-catenin signaling pathway. Issue 16 (April 2017) - Xiao, Zhili; Han, Yineng; Zhang, Yan; Zhang, Xiaonan
Abstract: Background: The aim of this study is to investigate the effects of hypoxia on the proliferation, morphology, migration ability, hypoxia inducible factor (HIF) 1 (HIF-1) expression, and the relationship with Wnt/β-catenin signaling of human periodontal ligament cells (hPDLCs) in vitro. Methods: hPDLCs (4th passage) cultured by the tissue culture method were randomly assigned to slight (5% O2 ), severe hypoxia (1% O2 ) groups, and the control (21% O2 ) group, respectively. From 1st to 7th day, the optical density values were detected, and the growth curve was described. Wound healing assay was done to observe the migration ability of hPDLCs under various O2 conditions. Then reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR) was used to detect the expression of cementum-related genes and Wnt signaling pathway-related genes. Further, RT-qPCR, Western blot, and immunofluorescence staining method were constructed to show HIF expressions under different O2 concentrations in hPDLCs. Results: The growth rate of hPDLCs decreased with the reduction of O2 content by degree, and the morphology of hPDLCs changed in different O2 contents. Besides, hPDLCs migrate faster in 21% and 5% O2 than in 1% O2, and both the expressions of cementum-related genes and Wnt signaling pathway-related genes were raised under hypoxic conditions. In addition, with the reduction of O2 concentration, the messenger RNA and protein level expression of HIF were all increased, and HIF was gradually transported from cytoplasm into the nucleus and in 1% O2 concentration, it was mainly expressed in the nucleus. Conclusion: This finding demonstrated that hypoxia was capable of suppressing the proliferation and migration ability, changing the morphology of hPDLCs, and stabilizing HIF-1α against degradation and promoting its translocation to the nucleus. Meanwhile, hypoxia may regulate hPDLCs proliferation and cementogenic differentiation via Wnt/β-catenin signaling pathway, which may potentially provide a novel insight into the etiology and treatment of periodontal diseases.